Evaluation of enlarged laminectomy with lateral mass screw fixation in relieving nerve root symptoms and correcting kyphosis for cervical myelopathy and radiculopathy - Fang, Zhao; Li, Yuqiao; Huang, Zongyu; Luo, Gan; Yang, Houzhi; Cheng, Haiyang; Xu, Tiantong (Frontiers in Surgery, 2023)
Purpose: This study aimed to compare the surgical efficacy of enlarged laminectomy with lateral mass screw fixation (EL-LMSF) and anterior cervical corpectomy decompression and fusion (ACCF) for multilevel cervical myelopathy and radiculopathy (CMR) related to kyphosis. Methods: We retrospectively analyzed 75 patients treated with either EL-LMSF or ACCF surgery for multilevel CMR in the study. Operative time, blood loss, the incidence of surgical complications, and the magnitude of the regional sagittal Cobb angle were compared. According to the Japanese Orthopedic Association (JOA) Scores, Visual Analog Scale (VAS) scores for the neck, radiological parameters and clinical function scores pre- and postoperatively were compared in each patient to analyze the surgical efficacy of EL-LMSF and ACCF. Results: The JOA score, VAS score for neck pain and C2-C7 angle before the operation were not significantly different between the ACCF group and the EL-LMSF group. The ACCF group was performed over a mean of 2.39 levels (range, 2-3 levels) and all patients were followed up for more than 1 year after surgery. Analysis of the follow-up data showed a shorter operation time (103 ±22 min vs. 125 ±37 min, P=0.000) and less blood loss (78 ±15 ml vs. 226 ±31 ml, P=0.000) in the ACCF group than the EL-LMSF group. Patients treated with EL-LMSF indicated lower VAS scores for the neck (1.3 ± 1.7 vs. 3.3 ± 1.3, P=0.003) and better cervical lordosis (10.7±4.2° vs. 8.5 ±3.5°, P=0.013) than the ACCF group.No difference in the JOA score (14.1±1.7 vs. 13.5±2.1, P=0.222) was noted between the two groups. During the follow-up period, 15.2% of patients in the ACCF group had complications, including 2 cases with transient dysphagia, 1 case with C5 palsy, 1 case with axial symptoms, and 1 with screw pullout. In the EL-LMSF group, only 9.5% of cases experienced complications, including 3 cases of axial pain and 1 case of epidural hematoma. Conclusions: EL-LMSF for the treatment of multilevel CMR is an effective and safe strategy for relieving nerve root symptoms and restoring cervical curvature. However, high-quality, large-scale clinical trials with long-term follow-up are urgently warranted.